If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y-12=7y-36
We move all terms to the left:
3y-12-(7y-36)=0
We get rid of parentheses
3y-7y+36-12=0
We add all the numbers together, and all the variables
-4y+24=0
We move all terms containing y to the left, all other terms to the right
-4y=-24
y=-24/-4
y=+6
| -7(x-3)+2=12 | | X-6=7/9x+10 | | 5x-8(2+4x)=3-2x+4 | | -18+14-17x=4x | | 6x+3=5x+4= | | 6x(x-5)=12 | | 2x-5=8x-15 | | 5x+3=2-4x | | (72t)−2=4+7t | | 72t)−2=4+7t | | 2x-100=x+2 | | 1/4+1/2+z=-3/4 | | 11=m–4 | | 2(39x-11)=2(17x+6) | | 39x-11=17+6 | | 39x-11=2(17x+6) | | -3/8-7x=-149/24 | | 2(39x-11)=17x+6 | | 9x+1=-1x+19 | | 14^-9x=3^x-5 | | 5x+5=2x+3+x | | -18x+14-17x=4x | | -15x+122=-8x+66 | | -8x-20=-5x-11 | | 2x-21=x-14 | | 10x+19=15x+29 | | -24x+99=-16x+51 | | -79=-1-6n | | 9p-9=18 | | 3p-6=-54 | | Y=2.3x+6 | | -12=(f-6) |